The Effect of Toxic Leadership on Conflict in the Workplace - Çiçek, Berat; Almalı, Vedat (Siirt University, 2020)
Based on the fact that leaders cannot always be perfect, on the contrary, some leaders may pose a danger to their environment, and this study aims to reveal the effect of toxic leadership on work in the workplace. In line with this purpose, quantitative research was carried out covering the manufacturing enterprises employees in the TRB-1 region (Malatya, Elazığ, Bingöl, Tunceli). According to the data collected by the survey method, it was concluded that toxic leadership increased the conflict in the workplace. Besides, it was observed that the adverse effects of toxic leadership increased as the employees’ tenure increased in their current jobs.
Keywords: Toksik Liderlik; Görev Çatışması; İlişki Çatışması; TRB-1 Bölgesi